Certification and Inspection Service Quality: Applying the fuzzy SERVQUAL method - CUI, Li-xin (Đại học Kinh tế, 2016)
This paper applied fuzzy set theory based on modified SERVQUAL model to analysis service quality in certification & inspection industry in China. The study consists of 405 randomly selected participants who are customers of China Certification & Inspection Group (CCIC). The paper includes four parts: introduction, methodology, a case study of certification & inspection service quality and conclusions. The results of this research show that among the five dimensions the feature of "tangible" has the biggest gap between the service quality expectations and perceptions. So, the company we studied (CCIC) need to increase investment in tangible aspects in order to improve their service quality efficiently.